دراسة أثر المتغيرات الاقتصادية والتكنولوجية على الاستراتيجيات التسويقية للمنظمات الخدمية ( دراسة ميدانية على فروع المصرف التجاري السوري في الساحل السوري) - نصور ريزان; محمد بسام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The study aimed to study the effect of some external marketing environment variables on strategic marketing planning in the banking sector. Independent variables were represented by (economic environment, technological environment), while the dependent variable represented strategic marketing planning (marketing message, marketing objectives, marketing strategy, and resources). The study community included the branches of the Commercial Bank of Syria in the Syrian coast (Lattakia - Tartous). The researcher conducted a comprehensive survey of all the vocabulary of the study society. A questionnaire was distributed to all managers and managers’ assistants in the branches of the Commercial Bank of Syria. With a response rate of 100%, and the data was analyzed using spss.The most important findings of the study were: 1- There is a statistically significant relationship between the economic environment and strategic marketing planning in the branches of the Commercial Bank of Syria in the Syrian coast. 2- There is a statistically significant relationship between the technological environment and strategic marketing planning in the branches of the Commercial Bank of Syria in the Syrian coast. هدفت الدراسة إلى دراسة تأثير بعض متغيرات البيئة التسويقية الخارجية على التخطيط الاستراتيجي التسويقي في القطاع المصرفي. ولقد تمثلت المتغيرات المستقلة بـ (البيئة الاقتصادية، والبيئة التكنولوجية)،في حين تمثل المتغير التابع بـالتخطيط الاستراتيجي التسويقي المتمثل بـ ( الرسالة التسويقية، الأهداف التسويقية، الاستراتيجية التسويقية، والموارد). وشمل مجتمع الدراسة فروع المصرف التجاري السوري في الساحل السوري ( اللاذقية – طرطوس)، وقام الباحث بإجراء مسح شامل لجميع مفردات مجتمع الدراسة، وتم توزيع / 122/ استمارة استبيان على جميع مدراء ومعاوني المدراء ورؤساء الأقسام في فروع المصرف التجاري السوري محل الدراسة وتم استردادها بالكامل وبنسبة استجابة بلغت 100%، وقد تم تحليل البيانات باستخدام .spss وكان من أهم النتائج التي توصلت إليها الدراسة: يوجد علاقة ذو دلالة إحصائية بين البيئة الاقتصادية والتخطيط الاستراتيجي التسويقي في فروع المصرف التجاري السوري في الساحل السوري. يوجد علاقة ذو دلالة إحصائية بين البيئة التكنولوجية والتخطيط الاستراتيجي التسويقي في فروع المصرف التجاري السوري في الساحل السوري.